First-Grade Cognitive Predictors of Writing Disabilities in Grades 2 Through 4 Elementary School Students. (July 2018) - Costa, Lara-Jeane; Green, Melissa; Sideris, John; Hooper, Stephen R.
The primary aim of this study was determining Grade 1 cognitive predictors of students at risk for writing disabilities in Grades 2 through 4. Applying cognitive measures selected to align with theoretical and empirical models of writing, tasks were administered to Grade 1 students assessing fine-motor, linguistic, and executive functions: 84 at risk (bottom quartile for age-base expectations) and 54 typically developing. A model with individual predictors was compared to a previously developed latent trait model to determine the relative predictive worth of each approach. Data analysis primarily involved stepwise logistic regression. Results revealed that the individual measures of orthographic choice, working memory, inhibitory control, visual memory recognition, and planning all were significant predictors of at risk status in Grades 2 through 4. The latent trait model also fared well but did not account for the same amount of variance as any of the individual measurement models for any of the grades. The findings lay the foundation for an empirically based approach to cognitive assessment in Grade 1 for identifying potential at-risk students in later elementary grades and suggest potential underlying neurocognitive abilities that could be employed with educational interventions for students with later-emerging writing disabilities.